Ghrelin: Central and Peripheral Implications in Anorexia Nervosa - Méquinion, Mathieu; Langlet, Fanny; Zgheib, Sara; Dickson, Suzanne; Dehouck, Bénédicte; Chauveau, Christophe; Viltart, Odile (Frontiers in Endocrinology, 2013)
Increasing clinical and therapeutic interest in the neurobiology of eating disorders reflects their dramatic impact on health. Chronic food restriction resulting in severe weight loss is a major symptom described in restrictive anorexia nervosa (AN) patients, and they also suffer from metabolic disturbances, infertility, osteopenia, and osteoporosis. Restrictive AN, mostly observed in young women, is the third largest cause of chronic illness in teenagers of industrialized countries. From a neurobiological perspective, AN-linked behaviors can be considered an adaptation that permits the endurance of reduced energy supply, involving central and/or peripheral reprograming. The severe weight loss observed in AN patients is accompanied by significant changes in hormones involved in energy balance, feeding behavior, and bone formation, all of which can be replicated in animals models. Increasing evidence suggests that AN could be an addictive behavior disorder, potentially linking defects in the reward mechanism with suppressed food intake, heightened physical activity, and mood disorder. Surprisingly, the plasma levels of ghrelin, an orexigenic hormone that drives food-motivated behavior, are increased. This increase in plasma ghrelin levels seems paradoxical in light of the restrained eating adopted by AN patients, and may rather result from an adaptation to the disease. The aim of this review is to describe the role played by ghrelin in AN focusing on its central vs. peripheral actions. In AN patients and in rodent AN models, chronic food restriction induces profound alterations in the « ghrelin » signaling that leads to the development of inappropriate behaviors like hyperactivity or addiction to food starvation and therefore a greater depletion in energy reserves. The question of a transient insensitivity to ghrelin and/or a potential metabolic reprograming is discussed in regard of new clinical treatments currently investigated.